Foliar and coarse root biomass in three forestry-drained boreal peatlands dominated by Downy birch (Betula pubescens Ehrh.) - Karim, Md Rezaul; Rinne-Garmston, Katja T.; Sarkkola, Sakari (Taylor & Francis, 2026)
Stand biomass in boreal forests has gained recognition for its crucial role in carbon cycling. While stand biomass is influenced by multiple factors, including stand age, tree species, and site fertility, stand age is often considered the most important factor. Most research has focused on conifer stands, with limited attention to foliage biomass and belowground biomass in peatland sites dominated by deciduous tree species. This study examined foliage and coarse root biomass allocation in three downy birch (Betula pubescens Ehrh.) stands on drained peatland sites in Central Finland. The stands represented three developmental classes: young (10 years), middle-aged (50 years), and mature (80 years). Results showed that foliage biomass ranged from 0.7 t ha−¹ to 6.6 t ha−¹¹, peaking in the middle-aged stand compared to the young and mature stands. Additionally, coarse root biomass in the 0–50 cm peat layer totaled 0.45 t ha−¹, 2.50 t ha−¹, and 1.10 t ha−¹ for the young, middle-aged, and mature stands, respectively, with 77% occurring in the top 20 cm layer. These findings enhance our understanding of biomass allocation patterns, particularly foliage biomass, over time and their impact on litter inputs into the soil.
Keywords: Above ground biomass; Coarse root biomass; Forest peatland; Stand age; Tree diameter